Effect of Fenugreek Vaginal Cream on Dyspareunia and Sexual Satisfaction in Menopausal Women: A Randomized Clinical Trial - Fakhriyeh Mazalzadeh; Khadija Hekmat; Foroogh Namjoyan; Amal SakiMalehi (Mashhad University of Medical Sciences, 2018)
Introduction: A great number of women undergo some variations in menopause due to the decreased release of estrogen. These changes may result in the reduction of sexual desire. Regarding this, the aim of the present study was to assess the effect of fenugreek vaginal cream on sexual satisfaction and dyspareunia in menopausal women. Methods: This double-blind randomized control trial was carried on 60 postmenopausal women referring to the healthcare center No. 1 of East Ahvaz, Iran, with the complaint of sexual dissatisfaction and dyspareunia in 2016. The participants were randomly assigned into two groups of intervention (n=30) and placebo (n=30). The intervention group received one applicator of fenugreek vaginal cream %5 once a day (5 g/day) for 8 weeks. The placebo group was also provided with the placebo administered within the same period. The research instruments included the Larson sexual satisfaction questionnaire measuring sexual satisfaction and an information form evaluating dyspareunia filled out before and after the intervention. Finally, the data were analyzed by using independent and paired sample t-test, Chi-square test, and Mann-Whitney U test in SPSS (version 22). P-value less than 0.05 was considered statistically significant. Result: According to the results,the intervention and placebo groups showed a significant difference in terms of the mean sexual satisfaction after the intervention (74.18±1.94-51.1±2.02) (P<0. 001). Conclusion: As the findings indicated, the application of fenugreek vaginal cream was effective in the reduction of dyspareunia and enhancement of sexual satisfaction in postmenopausal women.